The Effect Of Brand Import, Fashion Lifestyle Thriff Shop To Buying Interest (Case Study Of Universitas Muhammadiyah Bengkulu Students) - Wanda Setiawan; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2024)
on purchase intention (Case Study on Students of Muhammadiyah University of Bengkulu)